ANALISIS PELAYANAN LISTRIK PRABAYAR DI PT PLN (PERSERO) RAYON SEMARANG TENGAH (STUDI KASUS TENTANG PENANGANAN KELUHAN PELANGGAN LISTRIK PRABAYAR PT PLN (PERSERO) RAYON SEMARANG TENGAH - Yusi Ika Merlin; Nina Widowati; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The level of welfare and public services is directly proportional relationship. In connection with the assignment of PT PLN to serve and provide public service,so PT PLN has the creation of a quality service. The focus of research is the Prepaid Electricity program, especially customer service complaint handling prepaid electricity. The purpose of the study was to describe services handling customer complaints